Práticas populares utilizadas por gestantes de alto risco: existe suporte na literatura sobre essas práticas? - Suzuki, Liane Kiyomi (2013)
The usage of popular practices in order to either the treatment or prevention of both diseases and symptoms is very common along pregnancy, because of various maternal adaptations, frequent symptoms and requirement of special care. These popular practices are often regarded as healthy, beneficial and safe because they are "natural", however many plants are contraindicated because they may have toxic, teratogenic and abortifacient potential. The objective of study was to identify which popular practices (medicinal plants, homemade recipes and specific foods) are used by pregnant women at high risk for treatment and prevention of diseases or symptoms; to know the therapeutics indications; to check whether the information regarding these practices are cited sustention in technical literature, and if there are any contraindications throughout pregnancy. This is an clinical, cross-sectional and descriptive study done with 78 pregnant women who received medical and nutritional consultation on a clinic for high-risk cases at Maternity Santa Casa in São Carlos, within the period of April to July of 2012; these patients were interviewed based on a structured script, after the approval of the Ethics Committee and consent of the interviewees. For data analysis, it was used both simple descriptive statistics and chi-square tests. The results showed these pregnant women, in average, were 28.5 year-olds, and with 26.9 gestational weeks, which most of them were housewives, with family support; white, coming from the southeast; with 7 to 11 years of school; per capita income ½ to 1 minimum wage and evangelical religion. Independently of age, gestational age, ethnic groups, religion, education, income and region of origin, the pregnant women use the popular practices. From all the interviewed pregnant women, 64.10% confirmed the usage of some type of popular practice, related to symptoms of heartburn, flu, nausea, constipation, anxiety, diabetes, hypertension, cramps and others. Among the main popular practices used by the interviewed pregnant women, those with therapeutic indications are compatible with those described in the literature, except in the case of banana which effect over a cramp has not been scientifically proved. However, in many cases, their usage by pregnant women is contraindicated due to the teratogenic, abortive or toxic effects, such as in the cases of Boldo tea (Peumus boldus, Plectranthus barbatus), ginger (in high doses) (Zingiber officinale), immature papaya (Carica papaya), chamomile tea (Matricaria recutita), erva-cidreira tea (Melissa officinalis, Lippia alba, Cymbolponcitratus) and Melão-de-São-Caetano tea (Momordica charantia). To conclude, data about medicinal plants safety during pregnancy are scarce and often contradictory. More studies and researches are necessary about medicinal plants and popular practices done with teas, and not with plant extract, because this suggests that the quantities are excessively higher than those that would be consumed in teas. In the presence of any evidence suggesting risks for pregnancy, the usage of such plants should be avoided. The divulgation of results of this study should be done dialogically between health workers and users, so do not confront rather than ignore their cultural and popular knowledge, but that promotes reflection on their use of data obtained from the literature.